Gongylolepis martiana, an Asteraceae pollinated by bats in the Amazon. (7th June 2021) - Amorim, M. D.; Costa, D. da S.; Krahl, D. R. P.; Fischer, E.; Rech, A. R.
Abstract: Most Asteraceae species are pollinated by insects, mainly bees and butterflies, although pollination by birds has been documented and pollination by bats has been suggested for some species. Here, we investigated the pollination of Gongylolepis martiana, a species supposedly pollinated by bats. We assessed floral traits and visitors in a population of G. martiana in the Brazilian Amazon, measuring pollen removal from anthers and deposition on stigmas by diurnal and nocturnal visitors. Florets opened at dusk and lasted for 4 days, with the male phase starting on the first night and the female phase on the third night. Accumulated nectar per capitulum was 69.6 μl per night and sugar concentration was 15%. Nectar‐feeding bats and hummingbirds contacted the sexual parts, but pollen removal and deposition were greater throughout the night than during the day, when Meliponini bees considerably reduced pollen availability. Other nocturnal visitors of G. martiana were rare, including nocturnal bees and moths that foraged for pollen and nectar, respectively. Our results support that nectarivorous bats are the main pollinators of G. martiana, confirming Vogel's hypothesis of bat pollination in Asteraceae, particularly in the genus Gongylolepis . Since anthesis and each sexual floral phase started in the evening, nectarivorous bats and diurnal bees caused additive priority effects, preventing hummingbirds from being efficient pollinators. The high density of flowering individuals of G. martiana in patches from white‐sand forests likely increases bat attraction, while the small amount of nectar per plant favours cross‐pollination. Abstract : Floral traits and pollen removal from flowers and deposition on stigmas indicate the pollination of Gongylolepis martiana by nectar‐feeding bats, confirming the occurrence of chiropterophily in Asteraceae.